Moringa oleifera: A Medicinal Herb - Priyanka Dinkar Zerwal; Vishakha Patil; Vidya Dodwad; Allen Naorem; Pooja Pharne (Indian Journal of Dental Sciences)
Moringa oleifera Lam., also referred to as munga, is one of the most important plants that are widely farmed in India. It belongs to the family Moringaceae. A popular nutritional supplement, Moringa oleifera Lam possesses a number of advantageous pharmacological qualities, such as anti-inflammatory, anti-diabetic, anti-microbial, anti-oxidant, anti-allergic, wound healing and analgesic. The most extensively grown species of the monogeneric Moringaceae family, which is native to south Asia, is Moringa oleifera.